Team timeout calling in handball - Gomes, F.; Volossovitch, A.; Ferreira, A. P. (International Journal of Performance Analysis in Sport, 2014)
Team timeout (TTO) in handball is a powerful instrument that influences the team's performance. This study aimed to identify the different contexts of a TTO calling in handball according to the following contextual variables: 1) match status (current score difference), 2) goals scored in the last five ball possessions, 3) goals allowed in the last five ball possessions, 4) game period, and 5) match location. The sample consisted of 2178 TTOs registered in 720 match reports of official statistics of the ASOBAL League, seasons 2009/2010, 2010/2011 and 2011/2012. The results suggest that 71.0% of TTOs were called when the match status was "balanced" or "lose", 57.0% of TTOs occurred in the last ten minutes of each period and 57.9% of TTOs were called when the ratio between offensive and defensive short-term performances became negative. The interaction between match status, game period and short-term offensive and defensive performance was confirmed as the main source that causes handball coaches to call TTO. Further studies should focus on the contents of coaches' interventions during a TTO, as well as on its consequences on team performance in handball.